Electroconvulsive Therapy in a Longitudinal Transition From Early-Onset Obsessive-Compulsive Disorder to a Schizo-Obsessive Phenotype - Faruk Kurhan; Şükriye Ersen (The Journal of ECT, 2026)
Electroconvulsive therapy (ECT) is a well-established intervention for severe and treatment-resistant psychotic disorders; however, its domain-specific effectiveness across obsessive-compulsive and psychotic symptom dimensions within schizo-obsessive spectrum transitions is not well described. We report an 18-year-old female with severe childhood-onset obsessive-compulsive disorder (OCD) who, across adolescence, developed progressive insight erosion followed by referential delusions and tactile hallucinations. Across 3 consecutive hospitalizations, the clinical burden shifted from predominantly obsessive-compulsive pathology to psychosis-dominant symptomatology, prompting multimodal pharmacotherapy and repeated courses of ECT (total 12 sessions). Longitudinal symptom monitoring demonstrated partial and fluctuating improvement of obsessive-compulsive symptoms, while psychotic symptom severity showed marked and reproducible reduction following ECT courses, accompanied by global clinical improvement. This case highlights a clinically meaningful dissociation in treatment responsiveness, suggesting that ECT may preferentially ameliorate the psychotic dimension in schizo-obsessive spectrum presentations, whereas obsessive pathology may persist as residual burden, underscoring the importance of dimensional and stage-sensitive treatment planning.